Development of the Rhetorical Component in College Student Writing - Arenas Ulloa, César Ernesto (2025)
This article analyzes the impact of the instructional redesign of a course aimed at developing written communication skills, implemented in 2018 at a private university in Lima, Peru. The research is framed within the socio-discursive interactionism (SDI) model, which views writing as a situated practice shaped by specific communicative contexts. It also draws on the Writing Across the Curriculum (WAC) approach, which promotes writing as a transversal tool across all disciplines, emphasizing its cognitive (Writing to Learn), critical (Writing to Engage), and rhetorical (Writing in the Disciplines) dimensions. The study focused on the rhetorical component, adopting a quasi-experimental design with pre- and post-intervention assessments in two groups: experimental and control. The results show a moderate impact on the development of rhetorical competence, reflected in a greater alignment of students’ texts with academic prompts. This experience highlights the value of discourse genres as mediating tools in academic literacy processes, enabling students to engage actively in the discourse communities of their future professions.